2013
DOI: 10.2105/ajph.2013.301362
|View full text |Cite
|
Sign up to set email alerts
|

Marketing Little Cigars and Cigarillos: Advertising, Price, and Associations With Neighborhood Demographics

Abstract: Higher availability of LCCs in African American communities and lower prices and greater outdoor advertising in minority and young adult neighborhoods may establish environmental triggers to smoke among groups susceptible to initiation, addiction, and long-term negative health consequences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

10
126
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 131 publications
(136 citation statements)
references
References 58 publications
10
126
0
Order By: Relevance
“…Although there are no comparable data for retail advertising spent on non-cigarette combustibles, such as cigars, little cigars, cigarillos, and shisha, one recent study found higher levels of exterior advertising and lower prices of little cigars and cigarillos in neighborhoods with a greater proportion of young adults. 50 The strong association between outlet density and recent cigarette initiation among the older group of young adults was unexpected. While research indicates increasing cigarette initiation among young adults, the majority who initiate at this age do so between the ages of 18-24.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although there are no comparable data for retail advertising spent on non-cigarette combustibles, such as cigars, little cigars, cigarillos, and shisha, one recent study found higher levels of exterior advertising and lower prices of little cigars and cigarillos in neighborhoods with a greater proportion of young adults. 50 The strong association between outlet density and recent cigarette initiation among the older group of young adults was unexpected. While research indicates increasing cigarette initiation among young adults, the majority who initiate at this age do so between the ages of 18-24.…”
Section: Discussionmentioning
confidence: 99%
“…The strong positive association between density and recent cigarette and non-cigarette combustible product experimentation and the null association with recent noncombustible experimentation may be due either to varying availability of these products in outlets or differences in advertising at the point-of-sale. Although there is little data on variations in the availability of cigarettes, non-cigarette combustibles and noncombustibles across outlets, with some exceptions, [50][51][52] over 90% of cigarette marketing expenditures in the United States in 2011 7 were focused on the point-of sale environment compared with only 56% of noncombustible advertising dollars, which includes spending for chewing tobacco, dip/snuff, snus and dissolvables. 2 To reach the young adult population, relatively more resources for noncombustible marketing may be aimed toward sponsorships at bar nights and concerts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Demographic findings for both dual use groups mirror tobacco companies' targeted marketing, since tobacco companies market alternate, non-cigarette tobacco products to young adults, and have been shown to target black youth and young adults with cigar products, and white men with SLT products. 1,6,11,19 With regard to cigarette smoking behaviors, a significantly higher percentage of dual users of cigarettes and cigars, and cigarette-only users (respectively) reported smoking menthol, compared to dual users of cigarettes and SLT. This finding may be because tobacco companies have targeted both cigar and menthol cigarette promotions to similar demographic groups (eg, young adults, Blacks).…”
Section: Discussionmentioning
confidence: 99%
“…Another possible reason is that cigars include flavored products that have been heavily marketed to appeal to young adult and minority populations. 6,7 Young adults, in particular, may be trying a variety of tobacco products, 8,9 which could lead to dual use patterns.…”
mentioning
confidence: 99%